FORECASTING OF PRODUCTION OUTPUT FOR LIGHT INDUSTRY ENTERPRISES WITH PURPOSE TO DETERMINE THEIR POWER RESOURCES REQUIREMENTS. Part 2 - V. N. Romaniuk; D. B. Muslina (Наука и техника)
The proposed paper is a continuation of the work, published in the previous issue. It is destined for specialists who are engaged in solution of problems pertaining to efficiency of light industry in Belarus which is considered as one of the branches being significantly involved in formation of national economy, its export potential and social climate. It is extremely relevant to reduce production costs in order to preserve and add strength to the branch positions in the markets. Production of natural, synthetic and knitted materials and their subsequent treatment are unreasonably power-consuming processes. Fundamental solution of the problem for reduction of production costs is to decrease its energy component and this can be achieved due to transition to modern heat and power systems in technological complexes of enterprises.The first part of the paper has considered a range of issues that served as a basis for obtaining statistical models in order to forecast the required production volume of main knitted and textile materials.  Forecasting has been prepared   for a period of more than 20 years because it has been predetermined by development horizon of comprehensive modernization of energy supply systems at enterprises of light industry. The production volumes essentially differ from those that have been stipulated in the programs of light industry.The present paper shows selection of statistical game-type for determination of  build-up rate of the production volume for every textile enterprise. The so-called “Game with Nature” has been selected as a game which is widely used for solution of analogous demand problems. The statistical forecasting models of production obtained in the first part are applied in the second part of the paper which considers strategies for development of individual enterprises. JSC :Baranovichi Industrial Cotton Association” has been taken an example in the paper. Production volumes of any enterprise are determined on the basis of the development strategies with due account of risk minimization and obtaining maximum average expected profit. The average expected production of the enterprise is determined from these strategies in the light of minimizing risks and maximizing profits. Fundamental capacity of power consumption for designing their own cogeneration plants can be determined while using the concept of intensive energy saving. The concept prescribes  implementation of a systematic approach that takes into account the necessity of maximum utilization of secondary low-temperature production flows, specificity in consumption and generation schedules of energy flows, conditions of an industrial unit that includes the enterprise, requirements of the power system of Belarus under conditions of NPP operation.основе концепции интенсивного энергосбережения можно установить базовую мощность энергопотребления для проектирования собственных когенерационных установок. Концепция предписывает реализацию системного подхода, учитывающего необходимость максимальной утилизации побочных низкотемпературных потоков производства, специфику графиков потребления и генерации энергопотоков, условия промышленного узла, в который входит предприятие, и требования энергосистемы Беларуси в условиях работы АЭС.